The cognitive and pragmatic model of the English language-based research article macrostructure - Baibatyrova, А.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
Having an article published in the high index citation journals turns to be a considerable challenge for professional researchers, as well as novices writers. Writing such an article supposes not only deep awareness of the topic of investigation but also adequate skills to present the results in the form following the conventions in the English language academic culture. These canons include the abilities to structure a text according the its communicative and pragmatic purposes as well as semantic information, presented in the conventional sections of Introduction-Methodology-Result-Discussion (IMRD). This paper aims to show how IMRD is realized in 60 research articles from the high impact factor Humanities journals whose authors are experts in the academic discourse, genre and text studies. The main method is the quantitative analysis of the articles which contributed to the identification of most frequent models of the textual macrostructure, such as Abstract-Introduction-(Other Heading)-Methodology-Results-DiscussionConclusion и Abstract–Introduction-Methodology-(Results & Discussion)-Conclusion. Besides, the qualitative discursive analysis of the articles also enabled to distinguish the text fragments that clearly show the communicative purpose of an article section. The findings demonstrate that structuring a text is deeply cognitive as it includes knowledge of discipline, text organization and readers’ expectations. Structuring a text is also pragmatic because aims to convincingly present the research and have the perlocutionary effect from recipients. In this connection, this paper highlights the cognitive and pragmatic model of the macrostructure of the analyzed articles. The results of the investigation can be helpful for novice writers of empirical articles